Greece : Request for Stand-By Arrangement. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
Greek real GDP has declined by 2 percent in 2009, and indicators suggest that activity will weaken further in 2010. With the deteriorating fiscal results came downgrades of government bonds by rating agencies, and investors started backing out of Greek bonds, driving up their yields. Impaired loans are rising while borrowing costs in the interbank and wholesale markets have increased, putting pressure on bank profitability. The economy needs a strong and sustained adjustment program to correct fiscal imbalances and place debt on a downward path in the medium term.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet